Narrative Review : Characteristics Of Senilist Cataract Surgery Complications With Phacoemulsification Technique - Andi Dwyndha Pratiwi; Marlyanti Nur Rahmah; Diah Tantri Darkutni; A Faridah Amien; Hanna Aulia Namirah (Sean Institute, 2024)
Disease cataract is one of eye disorders human, cataract is condition Where lens eye experience turbidity caused Because hydration lens (additional fluid), denaturation of lens proteins or happen consequence both of them. Surgical action is governance definitive For cataract moment This, Purpose of Surgical Procedure cataract is For repair sharp vision consequence cloudy lens. Surgical technique phacoemulsification have excess like healing fast wound healing, repair vision more good, and no cause astigmatism post surgery. Regardless from benefit action surgery cataract with technique phacoemulsification that is For repair sharp vision, but action surgery cataract with technique phacoemulsification also does not off from complications that can occur happen Good during or after Operation. Research This is studies literature with approach narrative review. Reviewed literature is literature obtained from the database that has been accredited or indexed sinta. The result of studies literature This obtained that complications surgery senile cataract with technique phacoemulsification can cause complications intraoperative and also postoperative.